Influence of river runoff and precipitation on the seasonal and interannual variability of sea surface salinity in the eastern North Tropical Atlantic - C. Thouvenin-Masson; J. Boutin; V. Échevin; A. Lazar; J.-L. Vergely (Ocean Science)
In tropical regions, the freshwater flux entering the ocean originates primarily from precipitation and, to a lesser extent when considering basin-scale averages, from continental rivers. Nevertheless, at the regional scale, river flows can have a significant impact on the surface ocean dynamics. Riverine freshwater modifies salinity and, therefore, density, stratification, and circulation. With its particular coastline and high cumulative river discharge, as well as its being in the vicinity of the intertropical convergence zone (ITCZ), the eastern part of the North Tropical Atlantic (e-NTA) region off northwestern Africa is a particularly interesting location to study the linkage between precipitation, river outflow, and sea surface salinity (SSS). Here, we focus on the regional e-NTA SSS seasonal cycle and interannual variability and on the impact of using various river runoff and precipitation forcing data sets to simulate SSS with a regional model. The simulated SSS values are compared with the Climate Change Initiative (CCI) satellite SSS values; in situ SSS values from Argo floats, ships, and a coastal mooring; and the GLORYS reanalysis SSS values. An analysis of the mixed-layer salinity budget is then conducted. Overall, the simulations reproduce the seasonal cycle and interannual variability well despite a positive mean model bias north of 15° N. The seasonal cycle is impacted by the phasing of the different runoff products. The mixed-layer SSS decrease during the rainy season is mainly driven by precipitation followed by runoff by means of horizontal advection and is partly compensated for by vertical mixing. In terms of interannual anomalies, river runoff has a more direct impact on SSS than precipitation. This study highlights the importance of properly constraining river runoff and precipitation to simulate realistic SSS values and the importance of observing SSS in coastal regions to validate such constraints.